Aktivisme digital pemuda dan budaya populer dalam gerakan #ReformasiDikorupsi dan #TolakOmnibusLaw - Nida Dhiya Ulhak; Asti Lestari; Gina Aulia; Isna Quintana Maulani; Junaheni Afifah; Exsalliany Dewanty; Siti Komariah; Fajar Nughara Asyahidda (Dimensia: Jurnal Kajian Sosiologi, 2026)
This study examines the phenomenon of youth digital activism in the #ReformasiDikorupsi and #TolakOmnibusLaw movements, focusing on the sustainability of the movements until 2025. Unlike previous studies, this research highlights the use of pop culture as a new resistance strategy. Using qualitative methods with purposive sampling techniques, this study analyzes 80 viral posts on the X (Twitter) platform collected in October-November 2025. The results of the study show three main findings. First, the use of satirical memes such as “Dewan Pertahanan Raja” (King's Defense Council) effectively delegitimizes political institutions. Second, the appropriation of K-Pop culture (such as EXO song lyrics) expands the reach of the issue to non-political demographics. Third, this movement is hybrid in nature, where digital content such as the symbolism of the “Rat Statue” is used to mobilize real action. This study concludes that youth digital activism has evolved into a living collective memory that is able to adapt to contemporary cultural trends.